Decoding pain chronification: mechanisms of the acute-to-chronic transition - Zhang, Shunwei; Ning, Youzhi; Yang, Yiyi; Mu, Guo; Yang, Yongkui; Ren, Changhe; Liao, Changli; Ou, Cehua; Zhang, Yue (Frontiers in Molecular Neuroscience, 2025)
Pain chronification is a multidimensional and active pathophysiological process, not merely a consequence of prolonged nociception. This review proposes a four-domain mechanistic framework to elucidate the transition from acute to chronic pain. At the molecular-cellular level, persistent neuroinflammation-driven by activated glial cells and pro-inflammatory mediators such as TNF-α and IL-1β-leads to peripheral and central sensitization through enhanced excitability and ion channel dysregulation. In parallel, epigenetic mechanisms such as DNA methylation and histone modifications alter the expression of pain-related genes (e.g., SCN9A, BDNF), establishing a long-term transcriptional predisposition to chronic pain. These changes converge on maladaptive neural plasticity, characterized by aberrant synaptic strengthening, cortical map reorganization, and disrupted functional connectivity, which embed pain into persistent network states. Moreover, psychosocial factors-including catastrophizing, affective distress, and impaired top-down regulation-amplify pain through feedback loops involving the prefrontal cortex, amygdala, and hypothalamic-pituitary-adrenal (HPA) axis. By integrating these four interconnected domains, we highlight critical windows for mechanism-informed, temporally targeted interventions that may interrupt pain chronification and enable a shift toward proactive, personalized pain prevention.